Conceptual model of mobile augmented reality for engaging hearing-impaired museum visitors - Baker, Esraa Jaffar (2019)
Mobile Augmented Reality (MAR) has matured significantly over the past decades since the birth of multimedia system. It has evolved from the conceptual idea of augmented reality experience to its actual practical applications in use on smartphones. Researchers in MAR have resolved to employ the concept of engagement in designing MAR applications to attract museum visitors’ interest and ensure a more effective learning environment. However, most of these MAR applications are tailored to normal hearing visitors while the hearing-impaired (HI) visitors are less supported. This makes HI visitors to go through unpalatable experiences and eventually become dissatisfied with their visit to the museum. Also, there is lack of studies on the conceptual model of MAR for engaging the HI museum visitors. Therefore, this study proposes a conceptual model of MAR for the HI museum engagement (MARHIME) and eventually enhances their engagement during their museum visits. In achieving the aim of this study, design science research methodology was adapted. This study has determined engagement elements through expert review which were used to design the conceptual model of MARHIME. In addition, an MAR prototype was developed based on the MARHIME conceptual model and its architecture. The MARHIME prototype includes three-dimensional models, video, text, and images to deliver salient information of important artefacts to HI museum visitors. Moreover, the MARHIME application may only function in the museum by scanning the museum environment because the HI can use MAR as a visual signal guide in order to catch missing aural signals during their visit to the museums. The study involved 73 HI museum visitors as participants in order to evaluate the MARHIME prototype on their engagement experience. From the results of the evaluation, it was found that the MARHIME prototype was able to engage the HI visitors during their visit to the museum. Therefore, this study has validated a conceptual model on MAR for engaging the HI museum visitors. This conceptual model of MARHIME can be used as guidelines for researchers in understanding the elements of MAR in engaging the HI museum visitors and for developers in assisting the process of designing and developing MAR application for the HI museum visitors. This study contributes to the engagement of HI people during their museum visits to ensure the inclusiveness of disabled people in the MAR design.